2021
DOI: 10.31219/osf.io/gh4x7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontotemporal dementia is a complex disorder with a wide spectrum of clinical symptoms. Personalized medicine and gene therapy are promising strategies for treatment

Abstract: Frontotemporal dementia is an uncommon and complex sickness with a wide spectrum of clinical symptoms, making drug development for the condition challenging. Frontal and temporal lobe responsibilities, as well as the level to which these activities are affected in certain diseases, contribute to clinical heterogeneity. Unfortunately, the available data on symptomatic treatments is drawn from limited case studies and RCTs, which include persons with the same FTD diagnosis. Advances in the identification of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Several investigations have found that there are no significant changes in blood sRAGE levels between smokers and non-smokers (79). The inconsistency of the sRAGE level owing to cigarette smoking was discussed by Prasad et al (80). Smoking, on the other hand, causes a quick and substantial drop in serum sRAGE, according to research (81).…”
Section: In Copd the Age-rage Axis And Srage Play A Rolementioning
confidence: 99%
“…Several investigations have found that there are no significant changes in blood sRAGE levels between smokers and non-smokers (79). The inconsistency of the sRAGE level owing to cigarette smoking was discussed by Prasad et al (80). Smoking, on the other hand, causes a quick and substantial drop in serum sRAGE, according to research (81).…”
Section: In Copd the Age-rage Axis And Srage Play A Rolementioning
confidence: 99%
“…A large, cohort research comprising 132 participants with CKD discovered that urine ET-1 levels increased in individuals with SLE, even when their GFR was normal (72). Giant mesangial cell proliferation and matrix generation is associated with the presence of ET-1 in SLE patients (73,74). Renal ET-1 and ETB receptors are present in NZB/WF1 mice (34).…”
Section: Glomerulonephritis Renal Lupusmentioning
confidence: 99%
“…Transfection of the IL-6 gene inhibited tumor development in a mouse fibrosarcoma model (79). Furthermore, therapeutic immunization with autologous tumor cells expressing IL-6 and IL-2 prevents tumor growth in a lung metastasis model and results in total melanoma regression in a well-established metastatic mouse melanoma model (80).…”
Section: In Cancer Immunotherapy Cytokines Play An Important Rolementioning
confidence: 99%